EFEK MEDIASI SLACK DETECTION DAN KEADILAN DISTRIBUTIF TERHADAP HUBUNGAN PARTISIPASI ANGGARAN DAN SENJANGAN ANGGARAN - Nur Anita; Frida Fanani Rohma (AKUNTABILITAS, 2020)
Budgetary slack harms the company because it causes problems with future profits and resource losses. This study employed theory of planned behavior to investigate the effect of budget participation on budgetary slack by slack detection and distributive justice as a mediating variables. This study uses a survey with 111 managers and executive staff from various companies in Jakarta as participants. The results of the analysis using structural equation modeling show that budget participation has a positive effect on slack detection, and slack detection can reduce the tendency of budgetary slack. Further analysis shows that budget participation can increase distributive justice for individuals. However, the withdrawal of distributive justice triggers the tendency of budgetary slack. The results showed that budget participation could play a role as a two-point sword. Academics and practice need to be careful in interpreting the effectiveness of the role of budget participation as part of management control during budgeting